Studi Kualitas Air Kolam Ikan Air Tawar di Balai Benih Ikan Sentral Masni, Kabupaten Manokwari, Provinsi Papua Barat - Desy Nataliah; Alianto; Fitriyah Irmawati Ellyas Saleh; Fanny Fransina Carolina Simatauw; Fadli Zainuddin; Safar Dody (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Water quality parameters in pond include ammonia, nitrite, nitrate, phosphate, BOD, DO, turbidity, temperature, and pH. It is important to know the concentration of each component to properly minimize the negative impacts of their disturbances for the overall water quality and the biota in it. This study aims to determine the concentration of ammonia, nitrite, nitrate, phosphate, BOD, DO, turbidity, temperature, and pH in freshwater fish ponds at the Central Fish Seed Office (BBIS) of Masni, Manokwari Regency, West Papua Province. The study was conducted in May 2017, representing the rainy season, and August 2017, representing the dry season. Water samples were taken from settling, rearing, hatchery, and brood ponds. Meanwhile, standard method was implemented in the component measurements. The study results show that the concentrations of ammonia, nitrite, nitrate, and phosphate were 0.02-0.18 mg/L, 0.00-2.00 mg/L, 0.40-1.00 mg/L, and 1.01-21.83 mg/L, respectively. Furthermore, the concentrations of BOD and DO were 6.12-8.19 mg/L and 7.30-12.00 mg/L, respectively. Finally, the values of turbidity, temperature, and pH were 0.40-9.99 NTU, 26-30°C and 7.7-8.5, respectively.